2020
DOI: 10.1002/anie.202008630
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light Photoredox‐Catalyzed Remote Difunctionalizing Carboxylation of Unactivated Alkenes with CO2

Abstract: Remote difunctionalization of unactivated alkenes is challenging but a highly attractive tactic to install two functional groups across long distances. Reported herein is the first remote difunctionalization of alkenes with CO2. This visible‐light photoredox catalysis strategy provides a facile method to synthesize a series of carboxylic acids bearing valuable fluorine‐ or phosphorus‐containing functional groups. Moreover, this versatile protocol shows mild reaction conditions, broad substrate scope, and good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(51 citation statements)
references
References 154 publications
(1 reference statement)
0
46
0
5
Order By: Relevance
“…Very recently, Yu and co‐workers reported a reaction of unactivated alkenes with CO 2 via visible‐light photoredox catalysis to afford series of carboxylic acids (Scheme 18). [35] This reaction combines radical attack to alkenes, hydrogen atom transfer (HAT) and remote C−H functionalization. The radical precursors, including CF 3 SO 2 Na, CHF 2 SO 2 Na, and HP(O)Ph 2 , are used in the reaction.…”
Section: Photocarboxylation Via Reactive Intermediates Light‐driven Fmentioning
confidence: 99%
“…Very recently, Yu and co‐workers reported a reaction of unactivated alkenes with CO 2 via visible‐light photoredox catalysis to afford series of carboxylic acids (Scheme 18). [35] This reaction combines radical attack to alkenes, hydrogen atom transfer (HAT) and remote C−H functionalization. The radical precursors, including CF 3 SO 2 Na, CHF 2 SO 2 Na, and HP(O)Ph 2 , are used in the reaction.…”
Section: Photocarboxylation Via Reactive Intermediates Light‐driven Fmentioning
confidence: 99%
“…The structure of 2 was confirmed by X-ray analysis, representing a formal remote C-H carboxylation with CO2. [96][97][98] Control reactions revealed that no product was detected in the absence of either a PC or light, indicating the reaction was induced by light (entries 2 and 3). A significant decrease in the yield was observed when the reaction was carried out under nitrogen atmosphere (entry 4), suggesting that some CO2 could be produced from the oxidation of 4-CO2K-HE.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, dearomatization occurred predominantly at non-activated phenyl ring via 6-exo-trig cyclization rather than at the activated indole ring's C2-C3 double bond via 5-exo-trig in previous study with the same substrate, 90 leading to spirocyclic product 55 with a formal remote C-H carboxylation. [96][97][98] The rationale for this chemoselectivity is not clear at present. Initially, the iodide substrate was also employed, but it was less effective than its bromide analog (55).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the groups of Jamison [27] and Yu [28] have reported the synthesis of α‐AAs by α‐C−H functionalisation. Whereas Jamison's strategy proceeds by a radical–radical coupling of α‐amino radicals with CO 2 .− , Yu's proceeds by an intramolecular 1,5‐HAT, which generates the key α‐amino radical that can be subsequently reduced to the corresponding carbanion and trapped by CO 2 (Scheme 8 B,C).…”
Section: De Novo Synthesismentioning
confidence: 99%